2017
DOI: 10.1186/s12894-017-0294-3
|View full text |Cite
|
Sign up to set email alerts
|

Association of lower urinary tract symptoms and OAB severity with quality of life and mental health in China, Taiwan and South Korea: results from a cross-sectional, population-based study

Abstract: BackgroundLower urinary tract symptoms (LUTS) and overactive bladder (OAB) symptoms have a substantial effect on quality of life (QoL). We report QoL and mental health results from a LUTS prevalence study in three Asian countries.MethodsA cross-sectional, population-representative, internet-based study among individuals aged ≥40 years in China, Taiwan and South Korea. Instruments included: Overactive Bladder Symptom Score (OABSS); International Prostate Symptom Score (IPSS); other International Continence Soci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
32
1

Year Published

2019
2019
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(37 citation statements)
references
References 50 publications
2
32
1
Order By: Relevance
“…Some studies showed that the urinary symptoms, especially LUTS, impaired the QoL of patients and increased the tendency toward anxiety and depression. Therefore, an appropriate and effective treatment for symptom relief should be given . Because the etiology of KSM is unclear, currently, no effective medical therapy is available.…”
Section: Discussionmentioning
confidence: 99%
“…Some studies showed that the urinary symptoms, especially LUTS, impaired the QoL of patients and increased the tendency toward anxiety and depression. Therefore, an appropriate and effective treatment for symptom relief should be given . Because the etiology of KSM is unclear, currently, no effective medical therapy is available.…”
Section: Discussionmentioning
confidence: 99%
“…Overactive bladder (OAB), defined as “urinary urgency, usually accompanied by frequency and nocturia, with or without urgency urinary incontinence” (Herschorn et al., ), is highly prevalent in both men and women. This disorder severely impairs physical and psychological well‐being, social interactions, work productivity, sexual health, and quality of life (Coyne et al., ; Lee et al., ; Wang et al., ). It also places a substantial financial burden on individuals, society, and healthcare systems (Kelleher, ).…”
Section: Introductionmentioning
confidence: 99%
“…A global investment for scaling-up treatment on depression/anxiety found a benefit-to-cost ratio as 5.7-1 in depression and 3.3-1 in anxiety, both economic and value of health returns [14]. Epidemiolog-DOI: 10.1159/000497282 ical surveys have found relationships between depression/anxiety and OAB [5][6][7]15], and treatment of OAB [16][17][18][19][20][21] has been shown to improve depression and/or anxiety. The aim of this study was to evaluate the efficacy of mirabegron on OAB symptoms and its effects on the mental symptoms of treatment-naïve OAB women.…”
Section: Introductionmentioning
confidence: 99%
“…Epidemiological surveys have estimated the prevalence of OAB as 10-20% in adults, which increases with age [2-4]. OAB has a negative impact on the quality of life, performance of daily activities, sleep, personal relationships, and mental health [5][6][7]. Medical treatment is recommended after conservative treatment has failed [8,9].…”
Section: Introductionmentioning
confidence: 99%